2019
DOI: 10.3390/ani9080584
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Welfare Training on Bird Welfare and Carcass Quality in Two Commercial Poultry Primary Processing Plants

Abstract: The number of broilers slaughtered globally is increasing. Ensuring acceptable welfare conditions for birds at the time of slaughter is paramount in meeting legislative and retailer specifications, and in producing high quality meat. There is knowledge that welfare training programs for members of the farming and red meat slaughter industry can improve animal welfare measures and product quality, however there is little evidence of the effects of welfare training in poultry processing plants. In our study, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
1
0
1
Order By: Relevance
“…From this, the authors [87] concluded that "pigs can learn to perceive humans positively through observational social learning" (p. 127). Given this, the selection and training of staff is key [196][197][198], although the efficacy of such training depends on how it is administered [199].…”
Section: Spontaneous Social Learning Of Unanticipated or Negative Behmentioning
confidence: 99%
“…From this, the authors [87] concluded that "pigs can learn to perceive humans positively through observational social learning" (p. 127). Given this, the selection and training of staff is key [196][197][198], although the efficacy of such training depends on how it is administered [199].…”
Section: Spontaneous Social Learning Of Unanticipated or Negative Behmentioning
confidence: 99%
“…Aghwan et al (49) observaram resultados semelhantes e afirmaram que a sangria por meio de degola, precedida de atordoamento ou não, promove o BEA se realizado adequadamente. Neste sentido, Wigham et al (50) concluíram em seu experimento que treinamentos realizados com os operadores em frigoríficos de abate de frangos apresentaram efeitos benéficos sobre o procedimento de corte do pescoço. Além disso, verificaram movimentos mais suaves dos trabalhadores na pendura das aves, melhorias nos padrões de atordoamento e na ocorrência de pré-choque.…”
Section: Gestão Saúde E Transporte Nas Granjasunclassified